Ù‚ÙŠÙ…Ø© Ø§Ù„ØÙ†ÙŠÙ† ÙÙŠ Ø´Ø¹Ø± Ù…ØÙ…ÙˆØ¯ Ø¯Ø±ÙˆÙŠØ´ ÙˆÙƒÙŠØ§Ù‡ÙŠ Ø§Ù„ØØ§Ø¬ Ù…ØµØ·ÙÙ‰ Ø¨Ø³Ø±ÙŠ: Ø¯Ø±Ø§Ø³Ø© ÙÙŠ Ø§Ù„Ø§Ø¯Ø¨ Ø§Ù„Ù…Ù‚Ø§Ø±Ù† | The Value of Longing in the Poetry of Mahmoud Darwish and K.H. Mustofa Bisri: A Comparative Literature Study - Adnan Halim Husni,; Yeni Ratna Yuningsih,; Siti Saâ€™adah,; Merry Choirani,; Khairul Azmi,; R Yudha Alamsyah, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This article examines the value of longing in the poems â€œIlÄ UmmÄ«â€ by Mahmud Darwish and â€œIbuâ€ by K.H. Mustofa Bisri through a comparative literature approach. The study aims to explain how longing is constructed differently in two cultural contexts, Arab-Palestinian and Indonesian. The method employed is qualitative with a close reading technique, grounded in Raymond Williamsâ€™s Cultural Materialism approach, which views literary works as cultural practices. The analysis focuses on longing as a value that shapes human relations with the self, with others, and with the origins of life. The findings show that in Darwishâ€™s poetry, longing functions as a cultural response to experiences of alienation and loss, whereas in Gus Musâ€™s poetry, longing serves as an ethical reflection on sustained relationships. These findings confirm that longing is not merely a personal emotion, but a cultural value shaped by the social and historical conditions of the poet. This study contributes to comparative literature by positioning longing as an analytical category based on cultural context.